2021
DOI: 10.3390/neurosci2030019
|View full text |Cite
|
Sign up to set email alerts
|

Personality Profile and Low Back Pain: Are Clinicians Missing an Important Factor That Influences Pain Perception and Treatment Options?

Abstract: Personality type can influence pain perception and prognosis. Therefore, it is important for clinicians to consider personality factors that may influence outcomes and understand personality inventories to garner a better understanding of how an individual may perceive pain. This paper explores different elements that contribute to low back pain (LBP) and evaluates a personality inventory reported in the medical literature. Understanding how to evaluate personality type as well as how to approach clinical inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In general, this might decrease the statistical power of the analysis and reduce the number of IVs, though in this case it could be compensated by a very large sample size 27 . In addition, it is possible that we did not detect the expected causal effects of psychological factors because the back pain phenotype we used was not restricted to chronic back pain exclusively, while many previously described associations were observed specifically in the setting of chronic back pain 16,20,43 . Although we can hypothesize that patients with back pain seeking healthcare treatment most likely have chronic pain 15,21,35 , there may still be a substantial proportion of people with acute back pain in our GWAS sample and this might have affected our findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, this might decrease the statistical power of the analysis and reduce the number of IVs, though in this case it could be compensated by a very large sample size 27 . In addition, it is possible that we did not detect the expected causal effects of psychological factors because the back pain phenotype we used was not restricted to chronic back pain exclusively, while many previously described associations were observed specifically in the setting of chronic back pain 16,20,43 . Although we can hypothesize that patients with back pain seeking healthcare treatment most likely have chronic pain 15,21,35 , there may still be a substantial proportion of people with acute back pain in our GWAS sample and this might have affected our findings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, previously we have shown that major depressive disorder (MDD) has a moderate-magnitude causal association with chronic back pain (odds ratio [OR] = 1.41, 95% confidence interval [CI] 1.27; 1.58) 52 . This might be partially explained by central sensitization being more likely to develop in patients with anxiety and depression disorders and playing a vital role in the chronification of back pain 16,41 . On the other hand, disease experience may alter patients' behavior, for instance making them less prone to seeking new experiences and induce patients to control their movements carefully 20 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent review discussed the many contextual factors that frame the pain experience in patients with cLBP [7]. Socioeconomic status, level of education, and job satisfaction, as well as co-occurrence of mental health disorders such as depression and anxiety, have all been shown to impact the pain experience, especially as it relates to the development of chronic pain [1][2][3][4][5][6][7][8][9]. These findings confirm existing research showing connections between cLBP and psychological conditions, such as anxiety and depression [8,9].…”
Section: Introductionmentioning
confidence: 99%